All Days 1998
DOI: 10.4043/8809-ms
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design and Analyses of Deep-Sea FPSO Converted from VLCC

Abstract: As potential offshore oil fields shift from shallow water to deeper ocean, floating production, storage and offloading (FPSO) systems become more attractive than conventional huge fixed type platforms. Recently we have successfully completed conversion works of two FPSO's from old 280,000 DWT VLCC's and they will be towed and installed at Campos Basin, offshore Brazil. During this project elaborate hydrodynamic and structural analyses were performed to ensure proper function as an FPSO and to convince safety d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is also important to identify and evaluate which trading tanker systems can be reused or renewed, and which systems must be newly installed during conversion. Useful summaries of the information and practices associated with the conversion of trading tankers to ship-shaped offshore installations are given by Johnson (1996), Assayag et al (1997), da Costa Filho (1997, Park et al (1998), Parker (1999aParker ( , 1999b, Neto and de Souza Lima (2001), Terpstra et al (2001), Lane et al (2004), Mones (2004), Terpstra et al (2004) and Biasotto et al (2005).…”
Section: Selection Of a Suitable Tanker For Conversionmentioning
confidence: 99%
“…It is also important to identify and evaluate which trading tanker systems can be reused or renewed, and which systems must be newly installed during conversion. Useful summaries of the information and practices associated with the conversion of trading tankers to ship-shaped offshore installations are given by Johnson (1996), Assayag et al (1997), da Costa Filho (1997, Park et al (1998), Parker (1999aParker ( , 1999b, Neto and de Souza Lima (2001), Terpstra et al (2001), Lane et al (2004), Mones (2004), Terpstra et al (2004) and Biasotto et al (2005).…”
Section: Selection Of a Suitable Tanker For Conversionmentioning
confidence: 99%
“…For benign environments, it may be argued that the wave loads acting on the FPSO will be less than that corresponding to a tanker. For example Park et al [10] considered the case of an FPSO moored at Campos Basin, offshore Brazil. It was reported that the total value of the design bending moment is equal to about 60% of the value required by the rule approach.…”
Section: Environmental Loadingmentioning
confidence: 99%